Risk Factors Associated with Birth Asphyxia in Preterm Newborns: A Case Control Study - Safiullah; Farooq, Muhammad Azhar; Ghani, Usman; Muhammad Salman; Cheeme, Fatima Amir; Roohullah (Indus Journal of Bioscience Research, 2025)
Background: Birth asphyxia continues to be one of the most common causes of neonatal morbidity and mortality across the globe, especially among preterm infants who are more physiologically vulnerable. It remains one of the biggest problems in developing countries, such as Pakistan, regardless of the progress in obstetric care and neonatal care. Objective: The aim of the study was to determine maternal, obstetric, and neonatal risk factors linked to birth asphyxia in preterm infants at the Services Institute of Medical Sciences, Lahore. Methods: A case-control study was carried out in a hospital with unmatched cases between from 08 January 2025 to 08 June 2025. There were 240 preterm infants, of which 120 had asphyxia and 120 had no asphyxia. Primary data was gathered using maternal interviews, obstetric records, and neonatal examination. Logistic regression analysis was conducted to determine independent predictors of birth asphyxia. Results: Maternal age (age 30 years and above) (AOR=1.9, 95% CI: 1.13-3.5), no antenatal care (AOR=2.8, 95% CI: 1.6-4.9), preeclampsia (AOR=2.6, 95% CI: 1.25-5.7), prolonged labor (AOR=2.9, 95% CI: 1.5-5.6), and low birth weight (